Capillary irrigation by wick in the lettuce crop ( Lactuca sativa L.) in a combined system of hydroponic solution and soil, as an alternative in urban agriculture of Bolivia - P. Medrano-García; R. Chipana-Rivera; M.F. Moreno-Pérez; J. Roldán-Cañas (Ingeniería del Agua)
Some of the main cities of Bolivia are located in semiarid and arid zones, where there are recurrent droughts that cause rationing in the water supply. The present study was carried out in the Cota Cota Experimental Center, dependent on the Universidad Mayor de San Andrés, located in the city of La Paz at 3400 m.s.n.m. In that sense. the objective of the present work was to evaluate the wick irrigation in the lettuce crop ( Lactuca sativa L.) in combined system of soil and hydroponic solution, during two crop cycles. To do this, disposable plastic containers of 5 liters capacity were used. In one part of the container was placed the substrate (sand or loam) and in the other the hydroponic solution (FAO, La Molina and the Local) and cotton wick. Water consumption by transpiration in irrigation systems with and without wick was similar, however, there were highly significant differences in water yield and productivity in favor of the FAO solution, mainly in the second cycle. In this type of irrigation systems there was a great reduction in water consumption, and there is no additional energy expenditure, which is why it is an alternative for the cultivation of leafy vegetables, in small areas of land.